Small molecules enable cardiac reprogramming of mouse fibroblasts with a single factor, Oct4 - Wang, Haixia (2014)
It was recently shown that mouse fibroblasts could be reprogrammed into cells of a cardiac fate by forced expression of multiple transcription factors and microRNAs. To ultimately apply such reprogramming strategy for cell-based therapy or in vivo cardiac regeneration, reducing or eliminating the genetic manipulations by small molecules would be highly desirable. Here, we report the identification of a defined small-molecule cocktail that enables highly efficient conversion of mouse fibroblasts into cardiac cells with only one transcription factor, Oct4, without entering the pluripotent state. Small-molecule-induced cardiomyocytes spontaneously contract and exhibit a ventricular phenotype. Furthermore, such induced cardiomyocytes under our condition pass through a cardiac progenitor stage. This study lays the foundation for future pharmacological reprogramming approaches and provides a novel small-molecule condition to investigate the mechanisms underlying cardiac reprogramming process.